SPIRITUALITAS DALAM DOA BAPA KAMI - Nefry Christoffel Benyamin (Sekolah Tinggi Theologia Abdiel, 2018)
Generally, Christian prayer is related to the prayer taught by Jesus Christ, namely the Lord’s prayer. Christian community practices the Lord’s prayer in their worship, either in their family or in the Church. The question is “Do Christians understand and know the deep meaning of the prayer very well?” This question is important because the prayer talks about the intimate relationship between God and the believers. In this article, the writer tries to scrutinize the spiritual expressions of the prayer and to find the essence of the prayer that describes the manifestation of the believer’s love to God.